2001
DOI: 10.1097/00003226-200111000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Changes Induced by Contact Lens Wear

Abstract: This study confirms difference in expression of subclinical conjunctival inflammation in asymptomatic CL wearers, with lower levels for RCL than SCL wearers with daily or extended wear. The mucin system is also modified by this low but chronic aggression of the ocular surface, with a tendency to decrease with time in the RCL and SCL groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 16 publications
1
44
0
1
Order By: Relevance
“…This intolerance is generally associated with dry eye symptom resulting from chronic degenerative and mildly inflammatory changes of the conjunctiva and the corneal surface. 16 Apoptosis induced by multipurpose solutions could decrease the defence systems of the ocular surface, increasing the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This intolerance is generally associated with dry eye symptom resulting from chronic degenerative and mildly inflammatory changes of the conjunctiva and the corneal surface. 16 Apoptosis induced by multipurpose solutions could decrease the defence systems of the ocular surface, increasing the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…10 KCS and ocular rosacea were associated with overexpression of inflammatory markers such as HLA-DR and ICAM-1 and a significant decrease in the number of goblet cells. 29 Thus, in rosacea, inflammation of the ocular surface was clearly demonstrated with an increase of inflammatory mediators as interleukin (IL)-1a 30 or gelatinase B activity in tears of patients. 31 Hingorani et al 32 found a greater expression of HLA-DR in conjunctival epithelial cells in the different chronic ocular allergic disorders such as vernal keratoconjunctivitis (VKC) and atopic keratoconjunctivitis (AKC).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that in vitro conjunctival epithelium expresses HLA-DR, ICAM-1, CD40, and E-cadherin could suggest its role in initiation and regulation of ocular surface responses as well as its antigen-presenting properties. 33 Increased expression of HLA-DR and ICAM-1 has been reported in contact lens wearers compared to Flow cytometric analysis of HLA-DR antigen M Mrugacz et al normal eyes, 29 suggesting the possibility that contact lens use could cause inflammation of the conjunctiva. Our findings of a large number of HLA-DR þ conjunctival cells in CF patients confirm the presence of an inflammatory background and the immune nature of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…on numbers of polymorphonuclear leukocytes [29], tear cytokine profile [29] and increased expression of the inflammatory markers HLA -DR and ICAM-1 on ocular surface epithelia [30]. HLA-DR is a MHC class II antigen whose expression by conjunctival epithelial cells has been shown to correlate with the severity of dry eye, as characterised by vital staining and Schirmer test [31,32,33].…”
Section: Sub-clinical Inflammation Has Been Demonstrated In Contact Lmentioning
confidence: 99%